ÃâÃâSTOCK PRICE FORECASTING ACCURACY ANALYSIS USING MEAN ABSOLUT DEVIATION (MAD) AND MEAN ABSOLUTE PERCENTAGE ERROR (MAPE) ON SMOOTHING MOVING AVERAGE AND EXPONENTIAL MOVING AVERAGE INDICATORÃâÃâ (Empirical Study 10 LQ 45 Stock with Largest Capitalization from period Feb-Jul 2013) - Akbar Halimawan (NIM: 29111063) Pembimbing : Ir. Subiakto Sukarno, MBA., Alam
In investment in recent years suffered destruction when the U.S. stock market crisis in 2008 and led to the global financial crisis. Indonesia stock market crash of 2008, in general the majority due to external factors. The recovery of the world economy had a positive impact on economic growth in Indonesia. LQ 45 stock is a stock that has a market capitalization of 45 stocks are the most liquid and capitalized great. Based on the above the authors are interested in doing research and discuss Stock Price Forecasting Accuracy Analysis using Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE) on Smoothing Moving Average and Exponential Moving Average indikator Moving Average indicator provides information signal sale or purchase, as the determinant of the ongoing trend., Knowing the trend reversal (reversal), and Moving Average can be used to gain support and resistance. In general, there are several indicators to measure the accuracy of forecasting MAD, Mean Square Error (MSE) and MAPE.This study analyzes the results of a comparison of forecasting stock prices LQ 45 which has the largest market capitalization using the Smoothing Moving Average and Exponential Moving Average. Among these methods, which method has the highest accuracy in predicting stock prices, accuracy parameter used is MAD and MAPE. The samples used were the stocks that fall into the category LQ 45 in the period February 2013 - July 2013. The data used are the daily closing price of shares of LQ 10 45 which has the largest market capitalization. Result of Measurement showed that Comparison of MAD of 1 month (5-day of Smoothing Moving Average) is 187.087 and MAD of (Exponential Moving Average 5-day) is 166.944, comparison of MAPE of 1 month (5-day of Smoothing Moving Average) is 0.012 and the average MAPE of (Exponential Moving Average 5-day) is 0.011, comparison of MAD of 1 month (3-day of Smoothing Moving Average) is 187.087 and MAD of (Exponential Moving Average 3-day) is 145.292, comparison of MAPE of 1 month (3-day of Smoothing Moving Average) is 0.012 and the average MAPE of (Exponential Moving Average 3-day)is 0.009.Exponential Moving Average method recommended by the company and the investors by the author as having an average MAD and MAPE smaller than Smoothing moving average which indicates that the Exponential Moving Average has Measurement of Error smaller.